Advanced operating systems and kernel applications : techniques and technologies - Wiseman, Yair, 1970-; Jiang, Song (Information Science Reference, 2010)
"This book discusses non-distributed operating systems that benefit researchers, academicians, and practitioners"--Provided by publisher.